Caracterização química e atividades biológicas dos óleos essenciais e extratos alcoólicos das espécies Ocimum spp. (manjericão) e Curcuma longa (açafrão da terra) - Barbosa, Celma de Oliveira (2018)
The aromatic plants, Ocimum spp (Lamiaceae) and Curcuma longa (Zingiberaceae), have great economic, ecological and biotechnological potential of utility in medicine, Pharmaceutical industry and Food industry, for the production of essential oils and extracts with biological properties that can prevent chronic non-communicable diseases, neglected diseases like dengue, Zika and Chikungunya and Alzheimer's disease. The purpose of this study is to evaluate the chemical characteristics and the biological activities of the essential oils and alcoholic extracts of species of species of Ocimum spp. (basil) and varieties of Curcuma longa (saffron) as future biotechnological applications. The plants were supplied by Tropical Agroindustry Embrapa (CE), being extracted essential oils and prepared extracts of the species Ocimum spp. and Curcuma longa for analysis of chemical composition, antioxidant activity, inhibition of acetylcholinesterase, toxicity against Artemia salina and larvicide against Aedes aegypti. The composition of essential oils from Ocimum has shown great variability of chemotypes when compared to other localities, presenting a high content of eugenol in O. tenuiflorum, O. gratissimum, O. campechianum and O. basilicum (greek and ball varieties), and the samples showed a strong antioxidant potential in the methods analyzed, DPPH, ABTS and beta-carotene/linoleic acid methods, when compared to pure eugenol. Methyl chavicol was the major constituent of O. selloi; linalool and methyl-chavicol for O. basilicum var. “Maria Bonita”. The essential oils from the red variety of Curcuma longa had a higher content of alpha-turmerone, the white variety had 1,8-cineol as main constituent, and the ethanolic extract of red curcuma had a high content of total carotenoid, which conferred a better antioxidant potential to the extracts. All plants showed toxicity to Artemia salina, but eugenol-rich samples presented moderate inhibition for the acetylcholinesterase enzyme and strong larvicidal activity. Thus, the essential oils analyzed presented the chemotypes of eugenol, E-caryophyllene, methyl-chavicol, 1,8-cineol and alpha-turmerone, with a strong antioxidant and larvicidal potential in the species with eugenol content, adding value to the food industry, being able to be incorporated into new functional food or food biofilms for preservation or contributing to the control of chronic and neglected diseases